Baclofen prevented the changes in c-Fos and brain-derived neutrophic factor expressions during mecamylamine-precipitated nicotine withdrawal in mice - Varani, Andrés P. (2014)
Previous studies from our laboratory showed that baclofen (BAC, GABAB receptor agonist) prevented the behavioral and neurochemical alterations of nicotine (NIC) withdrawal syndrome. To further investigate the mechanisms underlying these effects, we analyzed the c-Fos and brain-derived neutrophic factor (BDNF) expression during NIC withdrawal and its prevention with BAC. Swiss-Webster mice received NIC (2.5 mg/kg, sc) four times daily, for 7 days. On the 8th day, NIC-treated mice received the nicotinic antagonist mecamylamine (MEC; 2 mg/kg, i.p.) 1 h after the last dose of NIC. A second group of NIC-treated mice received BAC (2 mg/kg, i.p.) prior to MEC administration. Thirty minutes after MEC, mice were sacrificed and the immunohistochemistry assays (c-Fos and BDNF) were performed at different anatomical levels. c-Fos expression decreased in the dentate gyrus of the hippocampus (DG) and the bed nucleus of the stria terminalis (BST), and increased in the habenular (Hb), accumbens shell (AcbSh) nuclei during NIC withdrawal. BAC re-established the modified c-Fos expression only in the DG, BST and AcbSh during NIC withdrawal. Conversely, BDNF expression decreased in the CA1 and CA3 area of the hippocampus, the Hb, and caudate putamen (CPu) during NIC withdrawal. Finally, BAC restored the decreased BDNF expression during NIC withdrawal in the CA1, CA3, Hb, and CPu. The results suggest a relationship between BAC's preventive effect of the expression of NIC withdrawal signs, and its ability to restore the changes in c-Fos and BDNF expression, observed in specific brain areas of NIC-withdrawn mice.